Toxicity of Food-Grade TiO2 to Commensal Intestinal and Transient Food-Borne Bacteria: New Insights Using Nano-SIMS and Synchrotron UV Fluorescence Imaging - Radziwill-Bienkowska, Joanna M.; Talbot, Pauline; Kamphuis, Jasper B. J.; Robert, Véronique; Cartier, Christel; Fourquaux, Isabelle; Lentzen, Esther; Audinot, Jean-Nicolas; Jamme, Frédéric; Réfrégiers, Matthieu; Bardowski, Jacek K.; Langella, Philippe; et al. (Frontiers in Microbiology, 2018)
TTitanium dioxide (TiO2) is commonly used as a food additive (E171 in the EU) for its whitening and opacifying properties. However, a risk of intestinal barrier disruption, including dysbiosis of the gut microbiota, is increasingly suspected because of the presence of a nano-sized fraction in this additive. We hypothesized that food-grade E171 and Aeroxyde P25 (identical to the NM-105 OECD reference nanomaterial in the European Union Joint Research Centre) interact with both commensal intestinal bacteria and transient food-borne bacteria under non-UV-irradiated conditions. Based on differences in their physicochemical properties, we expect a difference in their respective effects. To test these hypotheses, we chose a panel of eight Gram-positive/Gram-negative bacterial strains, isolated from different biotopes and belonging to the species Escherichia coli, Lactobacillus rhamnosus, Lactococcus lactis (subsp. lactis and cremoris), Streptococcus thermophilus and Lactobacillus sakei. Bacterial cells were exposed to food-grade E171 vs. P25 in vitro and the interactions were explored with innovative (nano)imaging methods. The ability of bacteria to trap TiO2 was demonstrated using synchrotron UV fluorescence imaging with single cell resolution. Subsequent alterations in the growth profiles were shown, notably for the transient food-borne L. lactis and the commensal intestinal E. coli in contact with food-grade TiO2. However, for both species, the reduction in cell cultivability remained moderate, and the morphological and ultrastructural damages, observed with electron microscopy, were restricted to a small number of cells. E. coli exposed to food-grade TiO2 showed some internalization of TiO2 (57% of cells), observed with high-resolution Nano-SIMS chemical imaging. Taken together, these data show that E171 may be trapped by commensal and transient food-borne bacteria within the gut. In return, it may induce some physiological alterations in the most sensitive species, with a putative impact on gut microbiota composition and functioning, especially after chronic exposure.